Professional Jurisdiction: an Exploration of the Police Experiences in Taking Indigenous Witness Statements - Zikalala, Nomsa Ingrid; Mofokeng, Jacob Tseko; Zenzile, Enoch; Motseki, Moses Morero (Journal of Current Social and Political Issues, 2024)
Research shows that the inaccurate translation of indigenous witness statements is a global phenomenon. This study was conducted to gain a better understanding of this phenomenon by exploring the experiences of South African Police Service (SAPS) members in taking indigenous witness statements. Using a qualitative method, interview schedules were administered to eighteen (18) SAPS members from nine Community Service Centres (CSC) in a township in the Gauteng province. Ethical considerations and measures of trustworthiness were applied to the study. Data were analyzed using Atlas.ti. The results showed that a majority of SAPS members reported there were no translators stationed at the designated CSCs, so they collaborated with colleagues to transcribe the indigenous witness statements into English. Five dominant themes emerged from the most regularly repeated responses: "skills," "collaboration," "resources," "duration," and "language." The Theory of Performance (ToP) was used to articulate these themes. Findings indicated that the SAPS members' levels of performance were influenced by their skills, available resources, time, and their collaboration in overcoming language challenges when transcribing indigenous witness statements. The conclusion drawn from this study is that the lack of translators at CSCs impacts the accuracy of indigenous witness statement translations, which is mitigated by the collaboration and skills of SAPS members. This research contributes to understanding the challenges faced in the translation process of indigenous witness statements and highlights the importance of providing adequate resources and training to improve police performance in this context.